Accident Analysiswork On Workers At The Glass Ambassador, Johan Pahlawan District, West Aceh Regency - Anastasya Putri Pohan, Farda; Jun Musnadi Is, Jun (CV. Inara, 2022)
Accident is an event that cannot be predicted and suspected by someone who experiences it which often results in losses both in terms ofmaterial and human life. The research method is carried out using descriptive qualitative research methods carried out through in-depth interviews (indept interviews). The results of the research conducted there are activities that are risky on human, mechanical andenvironmental factors at every stage of work at Duta Kaca. In the human factor, workers use PPE only glasses and masks if there is a need, and negligence is one of the triggers in working, on the mechanical factor. The available equipment also does not meet work standards, unfavorable machine conditions can also cause work accidents at Duta Kaca, In terms of the work environment, workers feel comfortable with their work environment and are accustomed to noise, so the environment does not trigger work accidents at Duta Glass. So it can be concluded that the aluminum service activities at Duta Kaca have risks that can be detrimental to the workers. It is suggested to the owners of Duta Kaca to pay more attention to workers to wearPersonal Protective Equipment.